1999
DOI: 10.1016/s0169-8095(99)00011-3
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of total lightning activity in severe Florida thunderstorms

Abstract: The development of a new observational system called LISDAD (Lightning Imaging Sensor Demonstration and Display) has enabled a study of severe weather in central Florida. The total flash rates for storms verified to be severe are found to exceed 60 flashes/rain, with some values reaching 500 flashes/min. Similar to earlier results for thunderstorm microbursts, the peak flash rate precedes the severe weather at the ground by 5-20 minutes. A distinguishing feature of severe storms is the presence of lightning "j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
175
1
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(211 citation statements)
references
References 25 publications
22
175
1
13
Order By: Relevance
“…Figures 6c and 6d depict the distributions of these quantities. The total FR measures confirm many previous studies in which severe thunderstorms were characterized by greater FRs than nonsevere storms (e.g., Williams et al 1999;Schultz et al 2011;Rudlosky and Fuelberg 2013). Figure 7c indicates that roughly 75% of nonsevere LD thunderstorms possessed maximum FRs below 25 fpm while 75% of severe LD thunderstorms possessed maximum FRs above 25 fpm.…”
Section: B Severe Versus Nonsevere Thunderstorm Lightning Trendssupporting
confidence: 88%
See 3 more Smart Citations
“…Figures 6c and 6d depict the distributions of these quantities. The total FR measures confirm many previous studies in which severe thunderstorms were characterized by greater FRs than nonsevere storms (e.g., Williams et al 1999;Schultz et al 2011;Rudlosky and Fuelberg 2013). Figure 7c indicates that roughly 75% of nonsevere LD thunderstorms possessed maximum FRs below 25 fpm while 75% of severe LD thunderstorms possessed maximum FRs above 25 fpm.…”
Section: B Severe Versus Nonsevere Thunderstorm Lightning Trendssupporting
confidence: 88%
“…The results indicate that 25 fpm could provide an anecdotal threshold differentiating between severe and nonsevere convection. Although this value is much smaller than the 60 fpm suggested by Williams et al (1999), it is very similar to the base flash rate threshold employed by the Earth Networks' DTA, and this relationship merits further investigation. Thought an LJA implementation is much more than a single flash rate threshold [i.e., warnings issued based purely on FR threshold exceedance have also struggled with POD and FAR (e.g., Meyer et al 2015)], the potential utility of 25 fpm as a regionally useful indicator for the central Appalachians should be explored.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous research has shown that rapid increases in lightning activity (i.e., lightning jumps) are highly correlated with the occurrence of severe weather (Williams et al 1999;Schultz et al 2009, hereafter S09; Gatlin and Goodman 2010)-using lightning data from available three-dimensional lightning networks throughout the United States. Furthermore, recent studies (S09; Gatlin and Goodman 2010;Schultz et al 2011, hereafter S11) have quantified the lightning jump based on statistical performance metrics, including probability of detection (POD) and false alarm ratio (FAR).…”
Section: Introductionmentioning
confidence: 99%